Natural capital dynamics in coastal planktonic systems: A biophysical accounting perspective - Daniele Bellardini; Luca Russo; Simonepietro Canese; Daniela Cianelli; Fabio Conversano; Priscilla Licandro; Chiara Paoli; Augusto Passarelli; Simona Saviano; Domenico D’Alelio; Paolo Vassallo (Marine Pollution Bulletin, 2026)

Big sharks in the dark: High densities of the bluntnose sixgill shark Hexanchus griseus in the Gulf of Naples - Simona Noè; Francesco Stenico; Frine Cardone; Antonio Terlizzi; Simonepietro Canese; Teresa Romeo; Chiara Bonaviri; Andrea Aiello; Trevor J. Willis (Ecology, 2026)

Expanding knowledge of deep-sea coronatae medusae (Cnidaria, Scyphozoa) in the Mediterranean through ROV-based in situ documentation - Frine Cardone; Antonio Giova; Simonepietro Canese; Valentina Costa; Martina Genovese; Teresa Romeo; Eva Salvati; Francesco Stenico; Silvestro Greco (Marine Biology, 2026)

Marine litter as a tool to enhance ecological restoration - Roberto Danovaro; Ettore Nepote; Cristina Gambi; Cinzia Corinaldesi; Simonepietro Canese; Antonio Dell'Anno; Giorgio Castellan; Federica Foglini; Silvestro Greco (Marine Pollution Bulletin, 2026)

No place to hide: Assessing habitat shifts of Benthocometes robustus from Cold-Water corals to marine litter in the Mediterranean Sea - Ludovica De Vincenzis; Pietro Battaglia; Valeria Palummo; Giacomo Milisenda; Simonepietro Canese; Frine Cardone; Daniela Pica; Eva Salvati; Francesco Stenico; Pierpaolo Consoli; Valentina Costa; Antonio Giova; et al. (Marine Environmental Research, 2026)

On Synagoga mira Norman, 1888 (Crustacea, Ascothoracida), associated with the black coral Parantipathes larix (Esper, 1788) - Marzia Bo; Giorgio Bavestrello; Alfredo Marchiò; Margherita Toma; Simonepietro Canese; Michela Angiolillo; Federico Betti (Marine Biodiversity, 2025)
Synagoga mira Norman, 1888 is a poorly known ascothoracidan that has never been reported since its original description in 1888, which was based on a few specimens recovered from colonies of the black coral Parantipathes larix (Esper, 1788) collected in the Gulf of Naples (Mediterranean Sea). A series of Remotely Operated Vehicle (ROV) campaigns conducted between 2006 and 2022 along the Italian coast (western Mediterranean Sea) identified numerous P. larix forests, allowing the investigation of the presence of S. mira on a broad geographical and bathymetric scale and the collection of twelve specimens. The first pictures of both in situ and collected specimens are reported here. The sexes seem separated and slightly skewed towards females. Synagoga mira , specialised in grazing the living tissue of P. larix , is confirmed overall as a rare species (19.2% of the sites with black coral forests between 109 and 251 m). The highest frequency of records (12 sites) and abundance of individuals (588) were confined to the Pontine Archipelago, a hot spot of occurrence of this black coral. Infestation occurred in up to 68.8% of the host colonies, with up to 46 individuals per infested colony. The health status of the coral colonies seems not to influence the infestation from S. mira . This study provides the first ecological data on an enigmatic and poorly known crustacean, also representing the first information for mesophotic ascothoracidans.

Porifera Associated with Deep-Water Stylasterids (Cnidaria, Hydrozoa): New Species and Records from the Ross Sea (Antarctica) - Barbara Calcinai; Teo Marrocco; Camilla Roveta; Stefania Puce; Paolo Montagna; Claudio Mazzoli; Simonepietro Canese; Carlo Vultaggio; Marco Bertolino (Journal of Marine Science and Engineering, 2024)
Stylasterid corals are known to be fundamental habitat-formers in both deep and shallow waters. Their tridimensional structure enhances habitat complexity by creating refuges for a variety of organisms and by acting as basibionts for many other invertebrates, including sponges. Porifera represent crucial components of marine benthic assemblages and, in Antarctica, they often dominate benthic communities. Here, we explore the sponge community associated with thanatocoenosis, mostly composed of dead stylasterid skeletons, collected along the Western and Northern edges of the Ross Sea continental shelf. Overall, 37 sponge species were identified from 278 fragments of the stylasterid Inferiolabiata labiata, of which 7 are first records for the Ross Sea, 1 is first record for Antarctic waters and 2 are proposed as new species. Despite the high biodiversity recorded in this and previous studies on Antarctic deep-sea communities, we are still far from capturing the true richness of Antarctic benthic assemblages. Long-term research programs designed to improve the knowledge of the deep-sea fauna inhabiting Antarctic waters are needed to support successful management and conservation plans, especially in this area, considered one of the main marine diversity hotspots worldwide.

Shedding Light on the Italian Mesophotic Spongofauna - Margherita Toma; Marzia Bo; Marco Bertolino; Martina Canessa; Michela Angiolillo; Alessandro Cau; Franco Andaloro; Simonepietro Canese; Silvestro Greco; Giorgio Bavestrello (Journal of Marine Science and Engineering, 2024)
An analysis of 483 remotely operated vehicle (ROV) dives carried out along the Italian coast on hard substrata at mesophotic depths (40–200 m) allowed an overview of the rich sponge diversity (53 taxa) of the deep continental platform to be obtained for the first time. About 40% of the potential actual species diversity was recognisable using ROV, suggesting that this group is among the richest yet underestimated using this technology in contrast to other megabenthic taxa. Additionally, the study allowed us to gather data on the current basin-scale distribution and bathymetric limits of five common and easily identifiable demosponges with up to 55% occurrence in the explored sites: Aplysina cavernicola, the group Axinella damicornis/verrucosa, Chondrosia reniformis, Foraminospongia spp., and Hexadella racovitzai. Four of these latitudinal distributions were characterised by high occurrence in the Ligurian Sea and a progressive decrease towards the south Tyrrhenian Sea, with an occasional second minor peak of occurrence in the Sicily Channel. In contrast, Foraminospongia spp. showed a maximum occurrence on the offshore reliefs and a second one in the North–central Tyrrhenian Sea, while it was almost absent in the Ligurian Sea. Trophic and biogeographic reasons were discussed as possible causes of the double-peak distributions. The vertical distributions support a more consistent occurrence of all considered taxa in deeper waters than previously known. This suggests that they may more typically belong to the mesophotic realm than the shallow waters, owing to a more extensive sampling effort in the deeper depth range. The five target taxa are typical or associated species of seven reference habitats in the recently revised UNEP/SPA-RAC classification. However, they may create such dense aggregations that they should be listed as new facies in the abovementioned classification.

Diel rhythms of fish frequentation in a temperate mesophotic antipatharian forest and sleeping behaviour of the red swallowtail perch Anthias anthias (Linnaeus, 1758) - Marzia Bo; Andrea Costa; Martina Coppari; Francesco Enrichetti; Giorgio Bavestrello; Aleandra Di Caro; Simonepietro Canese; Federico Betti (Marine Biology, 2024)
A 21-day continuous monitoring of a highly tridimensional forest of the black coral Antipathella subpinnata (Ellis and Solander 1786) was carried out in the NW Mediterranean Sea at 63 m depth using an autonomous lander to investigate the diel short-term dynamics of the vagile fauna associated to the forest. The survey allowed to assess several aspects of the forest attractiveness and its use, especially by the ichthyofauna, including (i) the diversity and shifts of the fish community inhabiting three layers of the environment (seafloor, canopy, water column) between four light phases (dawn, day, dusk, night), (ii) the diel rhythm in forest use of the red swallowtail perch Anthias anthias (Linnaeus 1758) and its sleeping behaviour in terms of fidelity towards resting sites, duration of rests, and awakenings triggers, and, finally, (iii) the influence of biotic and abiotic variables on the fish behaviour. Considering that, so far, only spot censuses have been carried out in these habitats, this study provides a dynamic approach to the study of biodiversity in temperate mesophotic coral forests and offers an insight into the functioning of these complex and vulnerable ecosystems.

Structural diversity of Leiopathes glaberrima populations in the strait of Sicily: from pristine to declining forests - Antonio Giova; Simonepietro Canese; Benedetta Zoe Donelli; Teresa Romeo; Silvestro Greco (Frontiers in Marine Science, 2024)
Introduction The black coral Leiopathes glaberrima is a key component of deep-sea animal forests of the Western Mediterranean and North-Atlantic hard bottoms. Due to its ecological role, biological characteristics and sensitivity to fishing activities, it has been included in the Annex II of the Barcelona Convention, listed as an endangered species in IUCN Red Lists, and recognized as an indicator of Vulnerable Marine Ecosystems by the FAO. Methods During a survey conducted in the Strait of Sicily, 140 ROV transects were carried out allowing the characterization of environmental preferences, associated fauna and population structure of L. glaberrima in the study area. Results and discussion 1020 colonies were distributed between 165 and 672 meters and arranged in 17 patches and isolated colonies. The average height was determined to be 40.9 ± 1.0 cm, with the range spanning from a minimum of 5 cm up to nearby 200 cm. Pristine colonies accounted for 62.9%, mainly constituted by small-sized individuals densely aggregated (up to 14.5/m2 in a single frame) in the eastern part of the area. 24.5% of the specimens were dead and localized in the western margin where we reported a rare case of mass mortality in the deep-sea environment and the first ever described for black corals, opening new scenarios regarding the possibility that these events can occur in environments previously considered safe from danger. The triggering causes of these events in inaccessible environments are actually only hypothesized, but it is not to be excluded that, sooner or later, a similar effect could potentially result from anthropogenic climate changes.

Mobility of the sea pen Pteroeides spinosum (Ellis, 1764) (Cnidaria: Scleralcionacea: Pennatuloidea) - Michela Giusti; Michela Angiolillo; Simonepietro Canese; Leonardo Tunesi (Marine Biodiversity, 2024)

Improving the knowledge base of Vulnerable Marine Ecosystems’ distribution in the Amendolara Bank (Ionian Sea) - VALERIA PALUMMO; GIACOMO MILISENDA; DANIELA PICA; SIMONEPIETRO CANESE; EVA SALVATI; NUNZIACARLA SPANÒ; TERESA ROMEO; SILVESTRO GRECO (Mediterranean Marine Science, 2024)
The Amendolara Bank was recently designated as a Site of Community Importance; however, information on its ecosystems remains limited, with a particular dearth of knowledge regarding the deeper zone (>100 m). Previous studies have discovered the existence of Vulnerable Marine Ecosystems (VMEs) within the bank, underscoring the necessity for more comprehensive data and its significance in terms of conservation in the Ionian Sea. This study aims to investigate various aspects of the bank using Remotely Operated Vehicles (ROVs) to shed light on the possible presence of VME indicator species, their relationship with environmental variables, their connection with the observed fish, and to assess anthropogenic impact via the identification of fishing gear within the study area. This present research provides new information on the biodiversity of the Amendolara Bank, revealing the presence of four VME indicator species including the first sightings of black coral Antipathella subpinnata and the precious red coral Corallium rubrum. Moreover, it provides evidence on the interaction between fish fauna and VME indicator species as well as signs of anthropogenic impact from abandoned, lost, or otherwise discarded fishing gear (ALDFG). These findings highlight the urgent need for additional research to improve the knowledge base on the biodiversity of this unique spot in the Ionian Sea which would in turn ensure the development and implementation of more effective conservation and management measures.

First records of Chionodraco hamatus nests in coastal areas of Terra Nova Bay (Ross Sea): a potential nesting area for the species? - Erica Carlig; Davide Di Blasi; Simonepietro Canese; Marino Vacchi; Susie Grant; Laura Ghigliotti (Marine Biology, 2024)

Effect of environmental and anthropogenic factors on the distribution and co-occurrence of cold-water corals - Valeria Palummo; Giacomo Milisenda; Simonepietro Canese; Eva Salvati; Daniela Pica; Augusto Passarelli; Nunziacarla Spanò; Teresa Romeo; Silvestro Greco (Frontiers in Marine Science, 2023)
Cold-water corals (CWCs) are bioengineering species that can increase habitat heterogeneity and improve the deep sea’s biological diversity and ecosystem functioning. Knowledge of their distribution provides a critical baseline for assessing the effect of natural and anthropogenic impacts on these important deep-sea habitats. The aims of this study are: i) provide new data on the spatial distribution of six CWCs species in the Strait of Sicily, ii) describe the principal environmental and anthropogenic variables that play a role in shaping their distribution, iii) identify hotspots in which individuals belonging to the various species co-occur. Presence-only data of six CWCs species, ten environmental variables (depth, slope, rugosity, aspect, flowdir, temperature, salinity, north bottom current, east bottom current, chlorophyll-a), and one variable relating to bottom trawling effort (Automatic Information System – AIS) were used to predict the suitable habitats. We used Maximum Entropy modelling (MaxEnt) approach and used the AUC (area under the receiver operating characteristic curve) and TSS (true skill statistics) to evaluate the model performance. The results showed excellent AUC, TSS and AUC’s standard deviation mean values for all six species. The validation show high predictive performance. MaxEnt identified slope, depth, and rugosity as the most important predictors, showing the highest percentage contribution for all six species considered. Throughout the study area, highlyinterspecific persistent density hotspot of CWCs co-occurrence were discovered, with a total extension of 4.05 km 2 where all species co-occur. Although studies on the effect of environmental and anthropogenic factors that impact the distribution of these species of conservation interest remain scarce, the results of this study offer useful guidance for decision-makers to develop necessary conservation measures.

In situ observations of three deep-sea cephalopods in the central Mediterranean Sea - Pietro Battaglia; Simonepietro Canese; Eva Salvati; Silvestro Greco (Marine Biology, 2023)

In situ observation of circadian rhythm of polyps’ opening and closing of the coral Dendrophyllia ramea (Linnaeus, 1758) - EVA SALVATI; CLAUDIO PROVENZANI; ANDREA D'AMBROSI; MARIA GRAZIA FINOIA; ELENA ROMANO; Simonepietro Canese (Mediterranean Marine Science, 2023)
A widespread population of the coral Dendrophyllia ramea has been revealed southeast of Syracuse (East Sicily, Italy) at around 75 m depth. Dendrophyllia ramea is an arborescent scleractinian coral, classified as “Vulnerable” in the Mediterranean IUCN Red List and listed in Annex B of the Barcelona Convention. It is considered rare because it is seldom recorded on the Mediterranean seabed. In situ observations of two selected colonies were carried out over three months using a custom-made underwater video recording system to increase knowledge about the ecology of the species, specifically its circadian rhythm. The area was also surveyed using a special navigation system integrated into a diver propulsion vehicle to map the colonies’ position and distribution. The rhythms of the opening and closing of Dendrophyllia ramea’s polyps during the day were studied and linked to environmental factors, such as temperature, water flow, and direction. The results show that Dendrophyllia ramea opens and closes its polyps according to its circadian rhythm and water flow in analogy with other anthozoans in different environments. The opening/closing frequency analysis showed that both colonies closed at least once daily with different periodicity; one colony closed on average a few hours earlier. This project gathered important information on D. ramea’s circadian rhythm, which is relevant for improving knowledge about the ecology of this species since it provides insights into its feeding behavior, reproduction seasonality, response to environmental changes, interactions with other species, and conservation needs.

Facies created by the yellow coral Dendrophyllia cornigera (Lamarck, 1816): Origin, substrate preferences and habitat complexity - Francesco Enrichetti; Margherita Toma; Giorgio Bavestrello; Federico Betti; Michela Giusti; Simonepietro Canese; Davide Moccia; Gianluca Quarta; Lucio Calcagnile; Franco Andaloro; Silvestro Greco; Marzia Bo (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

A baseline for the monitoring of Mediterranean upper bathyal biogenic reefs within the marine strategy framework directive objectives - Michela Angiolillo; Marzia Bo; Margherita Toma; Michela Giusti; Eva Salvati; Antonio Giova; Antonio Lagudi; Lorenzo Rossi; Matteo Collina; Fabio Bruno; Simonepietro Canese; Leonardo Tunesi (Deep Sea Research Part I: Oceanographic Research Papers, 2023)

Structure and status of the Italian red coral forests: What can a large-scale study tell? - Margherita Toma; Marzia Bo; Daniele Giudice; Simonepietro Canese; Alessandro Cau; Franco Andaloro; Michela Angiolillo; Silvestro Greco; Giorgio Bavestrello (Frontiers in Marine Science, 2022)
The precious coral Corallium rubrum (Linnaeus, 1758) is a charismatic Mediterranean species. A recent large-scale investigation along the Italian coast highlighted its widespread occurrence at mesophotic and upper bathyal depths, especially on coralligenous and bathyal vertical hardgrounds. The lack of morphometric data limited the considerations on the structure and health status of the populations, fundamental to identify the most vulnerable sites and the correct management actions. For this reason, a ROV dataset, consisting of 624 dives carried out between 40 m and 1825 m in the Ligurian Sea, Tyrrhenian Sea, and Sicily Channel, was analysed to extrapolate quantitative data to describe the populations. Ten random frames were obtained from each of the 170 sites hosting red coral. Density, height, and entanglement were evaluated for about 15700 colonies counted in the frames. The densest populations were mainly found between 40 m and 80 m, with a clear latitudinal density decrease. The mesophotic populations were characterized by both scattered and densely aggregated colonies, while the bathyal ones were dominated by sparse colonies. This study identified 17 major coral areas based on the geographic proximity of the sites hosting red coral and their topographic and oceanographic affinity. The size-frequency distribution of the heights was skewed towards the smaller classes in almost all populations, with a modal class between 2 cm and 4 cm. This study depicted a stress situation of the populations throughout the entire study area, which could be correlated also to the long-term harvesting pressure carried out in the basins. Two additional sources of direct mortality were pointed out in this study. Entanglement to artisanal and recreational fishing gear interested about 18% of the recorded colonies, mainly at mesophotic depths. Almost all populations suffered from mechanical entanglement, with the highest percentages in the Ligurian Sea and Sicilian areas. This study also highlighted a massive occurrence of recent deep mortality events, mainly along the eastern and southern coast of Sardinia and in the Campanian Archipelago. Thirty sites with extensive patches of dead colonies still in place were reported from 70 m to around 200 m, but their formation remains unclear.

Science and Dissemination for the UN Ocean Decade Outcomes: Current Trends and Future Perspectives - Francesco Caruso; Pietro Tedesco; Gerardo Della Sala; Fortunato Palma Esposito; Marco Signore; Simonepietro Canese; Teresa Romeo; Marco Borra; Claudia Gili; Donatella de Pascale (Frontiers in Marine Science, 2022)
The Ocean Decade (OD) is the name of a United Nations (UN) initiative devoted to ocean science for sustainable development. It started in 2021 and will provide an opportunity to create a new foundation, across the science-policy interface, to strengthen the sustainable management of oceans and coasts and, at same time, bring benefits for future generations. The OD will establish a common strategy to achieve the objectives of the 2030 Agenda for Sustainable Development and the other European Union (EU) and international agreements, such as the EU Marine Strategy Framework Directive (MSFD), the Marine Biodiversity Strategy and the UN World Assessment I and II aimed at preserving ocean health. Furthermore, the OD has several expected outcomes that concern different aspects of marine environment, including its enormous values for humans. Several entities will combine efforts to achieve these goals and science is at the forefront of the sustainable blue economy. Marine research is solving complex challenges through interdisciplinary approaches, revolutionizing our life and our interaction with the ocean. This review discusses recent advancements in science related to the OD outcomes. The role of new technology for ocean exploration and monitoring, the importance of omics science and biotechnology to deal with ocean pollution, and other innovative solutions are discussed. All of these are inspired by the idea of using marine resources in a sustainable way and without impacting in a negative way on marine ecosystems. The role of science communication is therefore considered a crucial issue to spread the OD messages and to reach the general public and stakeholders. Only by the integration of science, governance, industry and public, the OD will have any chance to succeed.

Basin-scale occurrence and distribution of mesophotic and upper bathyal red coral forests along the Italian coasts - MARGHERITA TOMA; MARZIA BO; RICCARDO CATTANEO-VIETTI; SIMONEPIETRO CANESE; MARTINA CANESSA; RITA CANNAS; FRINE CARDONE; LAURA CARUGATI; ALESSANDRO CAU; GIUSEPPE CORRIERO; MARIA CRISTINA FOLLESA; MARIA MERCURIO; et al. (Mediterranean Marine Science, 2022)
The analysis of 879 ROV dives carried out along the Italian coasts on hard substrata at mesophotic and upper bathyal depths (40-775 m) allowed us to evaluate the current basin-scale presence, relative abundance, bathymetric limits, and habitat preferences of one of the most charismatic Mediterranean habitat-former anthozoan species, Corallium rubrum (Linnaeus, 1758). The species is widespread, and its occurrence ranged from 13% of the explored sites in Ionian Calabria to a hotspot of approximately 80% in Sardinia. Population relative densities were generally low (

Sponges associated with stylasterid thanatocoenosis (Cnidaria, Hydrozoa) from the deep Ross Sea (Southern Ocean) - Gabriele Costa; Giorgio Bavestrello; Simonepietro Canese; Martina Canessa; Claudio Mazzoli; Paolo Montagna; Stefania Puce; Stefano Schiaparelli; Marco Bertolino (Polar Biology, 2022)

Species and habitats of conservation interest in the Ecologically and Biologically Significant Area of the Strait of Sicily: a contribution towards the creation of a Specially Protected Areas of Mediterranean Importance - PIERPAOLO CONSOLI; CHIARA ALTOBELLI; PATRIZIA PERZIA; MARZIA BO; ANTONIETTA ROSSO; GIUSEPPINA ALONGI; DONATELLA SERIO; SIMONEPIETRO CANESE; TERESA ROMEO; FRANCO ANDALORO (Mediterranean Marine Science, 2021)
In 2015, the Strait of Sicily, which includes several banks, was candidate as a future Specially Protected Area of Mediterranean Importance (SPAMI) by the Contracting Parties of the Barcelona Convention. In this context, the present study aims to provide the first biological and ecological characterisation of this poorly known area, focusing on habitats and species of conservation concern. Surveys were carried through a remotely operated vehicle (ROV) and allowed the identification of 19 habitat types, mostly considered of priority interest by the SPA/BD Protocol of the Barcelona Convention. A total of 269 taxa were also identified, mostly Porifera, Cnidaria and Pisces, among which 115 species are of conservation concern according to the International Union for Conservation of Nature (IUCN) Red Lists, the Habitats Directive, the Bern Convention, the SPA/BD Protocol and CITES. ROV surveys allowed some interesting observations on poorly known species and habitats. Results underlined that remarkable discrepancies in species conservation status assessment that exist between the several lists of protected species considered. The IUCN Red Lists, although not legally binding for European States, are the most complete, but, in spite of this, the conservation policies in the EU are largely focused on the Habitats Directive, which is really not exhaustive. An exhaustive and legally binding instrument to protect species of conservation concern at European scale is highly recommended. Acquired results could be useful for the delimitation of a future SPAMI or a network of Marine Protected Areas (including the investigated banks) and the identification of zones within them suitable for different area-based management measures.

The Challenge to Observe Antarctic Toothfish (Dissostichus mawsoni) under Fast Ice - Davide Di Blasi; Simonepietro Canese; Erica Carlig; Steven J. Parker; Eva Pisano; Marino Vacchi; Laura Ghigliotti (Journal of Marine Science and Engineering, 2021)
In situ observation of Antarctic toothfish (Dissostichus mawsoni) is challenging as they typically live at depths greater than 500 m, in dark and ice-covered Antarctic waters. Searching for adequate methodologies to survey Antarctic toothfish in their habitat, we tested a miniaturized Baited Remote Underwater Video camera (BRUV), deployed through holes drilled in the sea ice in the Ross Sea region, over three field seasons. In 2015 three BRUVs were deployed at McMurdo Sound, and paired with a vertical longline sampling. In 2017, three opportunistic deployments were performed at Terra Nova Bay. In 2018 seven deployments at Terra Nova Bay provided preliminary data on the habitat preferences of the species. The design and configuration of the mini-BRUV allowed to collect high-quality video imagery of 60 Antarctic toothfish in 13 deployments from the fast sea ice. The behaviour of fish at the bait, intra-species interactions, and potential biases in individual counting were investigated, setting baselines for future studies on the abundance and distribution of Antarctic toothfish in sea-ice covered areas. This work represents the first step towards the development of protocols for non-extractive monitoring of the Antarctic toothfish in the high-Antarctica coastal shelf areas, of great value in the Ross Sea region where the largest MPA of the world has recently been established.

The demersal fish assemblages of the infra and circalittoral coastal rocky bottoms of the Aeolian Archipelago (Central Mediterranean Sea) studied by Remotely Operated Vehicle (ROV) - IVAN CONSALVO; GABRIELE La MESA; SIMONEPIETRO CANESE; MICHELA GIUSTI; EVA SALVATI; MARCO LOIA; LEONARDO TUNESI (Mediterranean Marine Science, 2020)
Demersal fish assemblages on the rocky bottoms of the Aeolian Archipelago were investigated using a Remotely Operated Vehicle (ROV) within the framework of research activities aimed at drawing up the zoning proposal of a new Italian national marine protected area. Visual assessments were conducted around the seven main islands by means of a total of 36 ROV transects. Video material was divided into 3 parts belonging to 3 Archipelago sectors (Western, Central and Eastern) and into 3 depth ranges (20-50, 51-120, 121-190). Thirty taxa of teleosts (29 species and 1 genus) belonging to 16 families were recorded. The assemblages were numerically dominated by some schooling fishes, such as Anthias anthias, Callanthias ruber and Chromis chromis, which exhibited a depth related partitioning of space, and three non-gregarious species, i.e. Serranus cabrilla, Coris julis and Lappanella fasciata. In terms of species composition, the assemblages observed in the sectors of the Archipelago largely overlapped. No significant sector-related differences were detected in fish species richness, diversity and total density. Species composition and the investigated assemblage parameters were significantly affected by depth. The pattern of variation in species richness among depth ranges changed depending on the archipelago sectors. No significant interaction between the factors depth range and sector was observed for species diversity and total density. Diversity values at 20-50 and 121-190 m depth were similar and significantly higher than that at 51-120 m depth. Fish total density showed a clear decreasing trend with increasing depth, though significant differences were detected between the 20-50 and 51-120 depth layers and the deepest one. Overall, the demersal fish assemblage of the Aeolian Archipelago was poorly diversified and depleted, most likely due to overfishing. This information highlighted the importance of the adoption of specific measures aimed at the recovery of overexploited resources and the restoration of the whole marine ecosystems.

Keratose‐dominated sponge grounds from temperate mesophotic ecosystems (NW Mediterranean Sea) - Francesco Enrichetti; Giorgio Bavestrello; Federico Betti; Martina Coppari; Margherita Toma; Roberto Pronzato; Simonepietro Canese; Marco Bertolino; Gabriele Costa; Maurizio Pansini; Marzia Bo (Marine Ecology, 2020)
Differently from the North Atlantic Ocean, only few examples of sponge grounds are known from the Mediterranean Sea, mainly thriving in the deep sea. In this study, a novel temperate mesophotic ecosystem dominated by massive keratose sponges is reported from the Ligurian deep continental shelf. An extensive Remotely Operated Vehicle (ROV) survey allowed to study the structure and large‐scale distribution of this biocoenosis. The sponge grounds here described are highly fragmented, being formed by a large number of dense, discrete aggregations of Sarcotragus foetidus (up to 7.7 specimens/m 2 ) and other sponges, including Spongia lamella and Axinella polypoides . They mainly occur on flat, patchy and highly silted hardgrounds between 40 and 70 m depth. These sponge‐dominated ecosystems have an exceptionally wide spatial distribution, estimated to cover up to nearly 200 hectares, with the largest sponge grounds occurring along the westernmost part of the Ligurian coast, probably in relation to more suitable oceanographic conditions. The dominant sponge species reach considerable heights (up to 65 cm), greatly increasing the habitat three‐dimensionality and acting as poles of attraction for a diverse sessile and vagile fauna. In addition, the high abundance of the keratose sponge grounds at mesophotic depths might represent a larval source for shallow‐water populations that in the last decades have been stricken by several mass mortality events.

First record of a symbiotic relationship between a polyclad and a black coral with description of Anthoplana antipathellae gen. et sp. nov. (Acotylea, Notoplanidae) - Marzia Bo; Giorgio Bavestrello; Giorgia Di Muzio; Simonepietro Canese; Federico Betti (Marine Biodiversity, 2019)

Plastic Debris Occurrence, Convergence Areas and Fin Whales Feeding Ground in the Mediterranean Marine Protected Area Pelagos Sanctuary: A Modeling Approach - Maria Cristina Fossi; Teresa Romeo; Matteo Baini; Cristina Panti; Letizia Marsili; Tommaso Campani; Simonepietro Canese; François Galgani; Jean-Noël Druon; Sabina Airoldi; Stefano Taddei; Maria Fattorini; et al. (Frontiers in Marine Science, 2017)

The Ventotene Volcanic Ridge: a newly explored complex in the central Tyrrhenian Sea (Italy) - Marco Cuffaro; Eleonora Martorelli; Alessandro Bosman; Alessia Conti; Sabina Bigi; Filippo Muccini; Luca Cocchi; Marco Ligi; Giovanni Bortoluzzi; Davide Scrocca; Simonepietro Canese; Francesco L. Chiocci; et al. (Bulletin of Volcanology, 2016)

The Mediterranean deep-water kelp Laminaria rodriguezii is an endangered species in the Adriatic Sea - Ante Žuljević; Akira F. Peters; Vedran Nikolić; Boris Antolić; Marija Despalatović; Ivan Cvitković; Igor Isajlović; Hrvoje Mihanović; Slavica Matijević; Dawn M. Shewring; Simonepietro Canese; Christos Katsaros; et al. (Marine Biology, 2016)

Distribution and population structure of deep‐dwelling red coral in the Northwest Mediterranean - Michela Angiolillo; Andrea Gori; Simonepietro Canese; Marzia Bo; Cristina Priori; Giorgio Bavestrello; Eva Salvati; Fabrizio Erra; Michael Greenacre; Giovanni Santangelo (Marine Ecology, 2016)
Commercially harvested since ancient times, the highly valuable red coral Corallium rubrum (Linnaeus, 1758) is an octocoral endemic to the Mediterranean Sea and adjacent Eastern Atlantic Ocean, where it occurs on rocky bottoms over a wide bathymetric range. Current knowledge is restricted to its shallow populations (15–50 m depth), with comparably little attention given to the deeper populations (50–200 m) that are nowadays the main target of exploitation. In this study, red coral distribution and population structure were assessed in three historically exploited areas (Amalfi, Ischia Island and Elba Island) in the Tyrrhenian Sea (Western Mediterranean Sea) between 50 and 130 m depth by means of ROV during a cruise carried out in the summer of 2010. Red coral populations showed a maximum patch frequency of 0.20 ± 0.04 SD patches·m −1 and a density ranging between 28 and 204 colonies·m −2 , with a fairly continuous bathymetric distribution. The highest red coral densities in the investigated areas were found on cliffs and boulders mainly exposed to the east, at the greatest depth, and characterized by medium percentage sediment cover. The study populations contained a high percentage (46% on average) of harvestable colonies (>7 mm basal diameter). Moreover, some colonies with fifth‐order branches were also observed, highlighting the probable older age of some components of these populations. The Ischia population showed the highest colony occupancy, density and size, suggesting a better conservation status than the populations at the other study locations. These results indicate that deep dwelling red coral populations in non‐stressed or less‐harvested areas may diverge from the inverse size‐density relationship previously observed in red coral populations with increasing depth.

Distribution and ecology of the tube-dweller Ampelisca ledoyeri (Amphipoda: Ampeliscidae) associated with the hydrothermal field off Panarea Island (Tyrrhenian Sea, Mediterranean) - Valentina Esposito; Salvatore Giacobbe; Andrea Cosentino; Caterina Stefania Minerva; Teresa Romeo; Simonepietro Canese; Franco Andaloro (Marine Biodiversity, 2015)

Deepwater corals biodiversity along roche du large ecosystems with different habitat complexity along the south Sardinia continental margin (CW Mediterranean Sea) - Alessandro Cau; M. Cristina Follesa; Davide Moccia; Andrea Alvito; Marzia Bo; Michela Angiolillo; Simonepietro Canese; Enrico M. Paliaga; Paolo E. Orrù; Flavio Sacco; Rita Cannas (Marine Biology, 2015)

Calcification is not the Achilles’ heel of cold‐water corals in an acidifying ocean - Riccardo Rodolfo‐Metalpa; Paolo Montagna; Stefano Aliani; Mireno Borghini; Simonepietro Canese; Jason M. Hall‐Spencer; Andy Foggo; Marco Milazzo; Marco Taviani; Fanny Houlbrèque (Global Change Biology, 2015)
Ocean acidification is thought to be a major threat to coral reefs: laboratory evidence and CO 2 seep research has shown adverse effects on many coral species, although a few are resilient. There are concerns that cold‐water corals are even more vulnerable as they live in areas where aragonite saturation (Ω ara ) is lower than in the tropics and is falling rapidly due to CO 2 emissions. Here, we provide laboratory evidence that net (gross calcification minus dissolution) and gross calcification rates of three common cold‐water corals, Caryophyllia smithii , Dendrophyllia cornigera, and Desmophyllum dianthus, are not affected by p CO 2 levels expected for 2100 ( p CO 2 1058 μatm, Ω ara 1.29), and nor are the rates of skeletal dissolution in D. dianthus . We transplanted D. dianthus to 350 m depth ( pH T 8.02; p CO 2 448 μatm, Ω ara 2.58) and to a 3 m depth CO 2 seep in oligotrophic waters ( pH T 7.35; p CO 2 2879 μatm, Ω ara 0.76) and found that the transplants calcified at the same rates regardless of the p CO 2 confirming their resilience to acidification, but at significantly lower rates than corals that were fed in aquaria. Our combination of field and laboratory evidence suggests that ocean acidification will not disrupt cold‐water coral calcification although falling aragonite levels may affect other organismal physiological and/or reef community processes.

The coral assemblages of an off‐shore deep M editerranean rocky bank ( NW S icily, I taly) - Marzia Bo; Carlo Cerrano; Simonepietro Canese; Eva Salvati; Michela Angiolillo; Giovanni Santangelo; Giorgio Bavestrello (Marine Ecology, 2014)
In this study we characterized the deep assemblages dwelling at 200–250 m depth on a large shoal off C apo S t. V ito P romontory ( N orthwestern coast of S icily, S outh T yrrhenian S ea) by means of ROV ‐imaging. Two assemblages of suspension feeders, dominated by the gorgonian C allogorgia verticillata and by the black coral L eiopathes glaberrima , together with a tanatocoenosis of the colonial yellow scleractinian coral D endrophyllia cornigera , were examined. The three main species were significatively distributed into two areas corresponding to different habitat preferences: a more elevated hardground hosting black corals and a gently sloping, silted rocky bottom hosting the other coral species. The study area is subjected to a heavy pressure from the professional fishery, resulting in the mechanical damage of numerous colonies, some of which are then overgrown by various epibionts including a parasitic bioluminescent zoanthid, new for the Mediterranean fauna, and tentatively identified as I sozoanthus primoidus . In the M editerranean S ea, these deep off‐shore rocky banks are widely known among recreational and professional fishermen due to their rich fish fauna. However, there has been still little effort into quantifying and characterizing the extent of the impact and its consequences on the benthic communities, which may represent, as in this case, only a partial picture of their original structure and extent.

Spatio-temporal movement patterns of Diplodus vulgaris (Actinopterygii, Sparidae) in a temperate marine reserve (Lampedusa, Mediterranean Sea) - Gabriele La Mesa; Ivan Consalvo; Aldo Annunziatellis; Simonepietro Canese (Hydrobiologia, 2013)

Role of deep sponge grounds in the Mediterranean Sea: a case study in southern Italy - Marzia Bo; Marco Bertolino; Giorgio Bavestrello; Simonepietro Canese; Michela Giusti; Michela Angiolillo; Maurizio Pansini; Marco Taviani (Hydrobiologia, 2012)